2017
DOI: 10.1021/acs.jpcb.7b01776
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Experimental and Simulation Approach To Explore the Underlying Mechanism of Denaturation of Stem Bromelain in Osmolytes

Abstract: Characterization of a protein in the context of its environment is of crucial importance for a complete understanding of its function. Although biophysical techniques provide powerful tools for studying the stability and activity of the enzyme in the presence of various cosolvents, an approach of combining both experimental techniques and molecular dynamic (MD) simulations may lead to the mechanistic insight into the interactions governing the stability of an enzyme. The knowledge of these interactions can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…The obtained Tm values of SB in the presence of IL, DES, and HIF are presented in Figure 3 and also provided in Table S1. For native SB, the transition temperature (T m ) was found to be 64.1 °C, which is consistent with the literature value; 36 later, the T m values decrease, which significantly decreases with increase in the concentration of IL (Figure 3). Also, the thermal transition curves have been provided in Figure S5.…”
Section: ■ Introductionsupporting
confidence: 90%
“…The obtained Tm values of SB in the presence of IL, DES, and HIF are presented in Figure 3 and also provided in Table S1. For native SB, the transition temperature (T m ) was found to be 64.1 °C, which is consistent with the literature value; 36 later, the T m values decrease, which significantly decreases with increase in the concentration of IL (Figure 3). Also, the thermal transition curves have been provided in Figure S5.…”
Section: ■ Introductionsupporting
confidence: 90%
“…[32][33][34][35] While it has been found that denaturing action of urea is generally enhanced by temperature, 36,37 the effect of temperature on protein stabilization by osmoprotectants is more complex. 33,35,38 In particular, it has been observed that at room temperatures betaine and similar protectants (sarcosine, glycine and proline) usually act as relatively weak stabilizers and may even slightly destabilize some proteins. However, as temperature increases, their stabilizing effect is also markedly enhanced (e.g., the effect of betaine on the unfolding free energy of cytochrome c changes from E0 kcal mol À1 at 293 K to 0.6 kcal mol À1 at 353 K).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the addition of ILs initiated the refolding of the protein structure, which eventually leads to movement of Trp residues toward the hydrophobic core of the protein. 41 As depicted in Figure 1a,c, the IL-1 is a more efficient refolding agent for both the serum albumins, namely BSA and HSA, respectively. Based on these results, refolding of ureadenatured serum albumins was successfully achieved under optimized IL concentration (i.e., 10 −5 M for BSA and 10 −4 M for HSA).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Addition of ILs to the denatured protein leads to enhanced fluorescence intensity accompanied by a blue shift in the emission maxima. Thus, the addition of ILs initiated the refolding of the protein structure, which eventually leads to movement of Trp residues toward the hydrophobic core of the protein …”
Section: Resultsmentioning
confidence: 99%